2016
DOI: 10.1002/bsl.2247
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Innocents' Naiveté: Pre‐interrogation Decision‐making Among Innocent Suspects

Abstract: Suspects, especially innocent ones, are highly susceptible to waiving their interrogation rights. This research tested the ability of two strategies to overcome innocent suspects' willingness to waive their rights. One strategy was based on the social influence of scarcity (i.e., not constraining the pre-interrogation time limit). The other strategy focused on disrupting individuals' cognitive fluency during the decision-making process (i.e., violating their induced expectation of offering a waiver). Disruptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Converging evidence from independent studies has confirmed and extended this innocence effect on Miranda waivers in a study conducted in Canada (Moore & Gagnier, 2008), especially among participants who strongly believe in a fair and just world (Scherr, Alberts, Franks, & Hawkins, 2016), and even among those who fully understood the administration of rights (Scherr, Normile, Bierstetel, Franks, & Hawkins, 2018). In other studies, innocent participants were more likely to waive their right to a full lineup in lieu of an immediate showup, complacent in the belief that they would not be misidentified (Holland, Kassin, & Wells, 2005); freely disclosed information to interrogators without apprehension of the consequences (Hartwig, Granhag, Strömwall, & Kronkvist, 2006; Hartwig, Granhag, Strömwall, & Vrij, 2005); and offered alibi stories without regard for the inconsequential errors that police might view as inculpatory (Olson & Charman, 2012).…”
Section: Stage 1: Precustodial Interviewmentioning
confidence: 89%
“…Converging evidence from independent studies has confirmed and extended this innocence effect on Miranda waivers in a study conducted in Canada (Moore & Gagnier, 2008), especially among participants who strongly believe in a fair and just world (Scherr, Alberts, Franks, & Hawkins, 2016), and even among those who fully understood the administration of rights (Scherr, Normile, Bierstetel, Franks, & Hawkins, 2018). In other studies, innocent participants were more likely to waive their right to a full lineup in lieu of an immediate showup, complacent in the belief that they would not be misidentified (Holland, Kassin, & Wells, 2005); freely disclosed information to interrogators without apprehension of the consequences (Hartwig, Granhag, Strömwall, & Kronkvist, 2006; Hartwig, Granhag, Strömwall, & Vrij, 2005); and offered alibi stories without regard for the inconsequential errors that police might view as inculpatory (Olson & Charman, 2012).…”
Section: Stage 1: Precustodial Interviewmentioning
confidence: 89%
“…When the waiver was characterized as being unimportant in this regard, innocent suspects waived their rights at higher rates than when the waiver was characterized as important (81% vs. 62%). Likewise, the use of implicit waivers—a strategy in which police read suspects their Miranda rights and then launch into questioning without asking suspects whether they understand or want to invoke their rights—not only increases the waiver rate (e.g., Scherr, Alberts, Franks, & Hawkins, 2016) but also leads suspects to make more self-incriminating statements relative to when a waiver was requested explicitly (Gillard, Rogers, Kelsey, & Robinson, 2014). In short, these studies suggest that the subtle but lawful social-influence strategies used routinely by police to administer Miranda warnings serve to increase the waiver rate, even among innocent suspects.…”
Section: “Voluntarily”: a Waiver Free Of Police Coercionmentioning
confidence: 99%
“…People are best able to remember and understand information when it is presented to them on several occasions, over an extended period of time (Vermunt, 1996). It has also been shown that people are better able to understand complex information when they are given a non-restrictive time frame to do so, and they are shown the information in written form (Rogers, Steadham, et al, 2016;Scherr, Alberts, Franks, & Hawkins, 2016).…”
Section: Participant's Understandingmentioning
confidence: 99%
“…Furthermore, the way the Rights Caution is presented to young people should perhaps be revised to assist them in remembering, understanding, and exercising their rights. For example, the rights could also be given to young people in written form, with more time allowed for them to go over each right individually (Rogers, Steadham, et al, 2016;Scherr et al, 2016). Additionally, perhaps a guardian or lawyer should always be present when a young person is being questioned by police to reduce the disadvantages that they experience due to immature decision making abilities, and the innate power imbalance present in such situations (Freedman et al, 2014;Medford et al, 2003).…”
Section: Conclusion and Further Suggestionsmentioning
confidence: 99%